2016
DOI: 10.1097/hco.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding and thrombosis in chronic ventricular assist device therapy

Abstract: Purpose of review LVADs have markedly improved the survival for patients with advanced heart failure but are plagued with significant morbidity, including pump thrombosis and bleeding. Better understanding of the platelet, and their role in the balance of bleeding and thrombosis, stands to impact the frequency and treatment of these significant complications. Recent findings In patients with LVADs, there is little consistency linking traditional biomarkers of platelet activation and clinical events. A number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
1
44
0
2
Order By: Relevance
“…Despite the significant progress in MCS clinical use, MCS therapy is not free of undesirable consequences. The significant complications with MCS, such as thrombosis and bleeding, were associated with worsening morbidity and mortality . Almost all contemporary MCS devices employ a rotary blood pump to pump the blood in the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant progress in MCS clinical use, MCS therapy is not free of undesirable consequences. The significant complications with MCS, such as thrombosis and bleeding, were associated with worsening morbidity and mortality . Almost all contemporary MCS devices employ a rotary blood pump to pump the blood in the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The need to examine platelet behavior during and after dynamic, device-related flow conditions was highlighted by the observation of chronic platelet activation and thromboembolic events in mechanical heart valve patients despite antiplatelet therapy (Butchart et al, 2003). These complications still remain a challenge for current VAD recipients (Koliopoulou et al, 2016). Starting in the early 2000s, researchers began examining platelet activation in response to complex non-physiological fluid shear stress waveforms utilizing markers including thrombin and P-selectin (Zhang et al, 2003; Zhang et al, 2002).…”
Section: Additive Platelet Damage As a Mechanism Of Activation – Tmentioning
confidence: 99%
“…The loss of high molecular weight multimers (HMWM) of VWF (named as acquired von willebrand syndrome) was observed in almost all patients with rotary pump MCS devices and has been suggested to contribute to the increased events of bleeding in these patients . Since platelets play the important role in initiating the normal hemostasis, HMSS‐induced platelet dysfunction may also be an important factor for the hemostatic dysfunction in patients with MCS. Previous studies revealed that high shear stresses can induce platelet activation .…”
Section: Introductionmentioning
confidence: 99%